The Characteristics of the Dialect Words Expressing Religious Beliefs - MESROPYAN, HAYKANUSH (Bulletin of Yerevan University B: Philology, 2021)
In this article the concepts “to believe” and “belief” and the dialect expressions associating with them are discussed. In the Armenian dialects,these words generally appear in phonetic variations with a limited number of synonyms. The majority of the Armenians dialect speakers (except for those living in the area of Western Armenia, in Chemlihemshin and Middle Asia) are the followers of Jesus Christ and they have religious vocabulary according to this faith. The dialect speakers in a negative way distinguish the fact of instability of the faith and the practice of other beliefs. There are a number of words in the Armenian dialects which are peculiar to people who have Christian parents and those who follow other beliefs.